A WEB-BASED MODEL FOR INSPECTION INCONSISTENCIES RESOLUTION: A NEW APPROACH WITH TWO CASE STUDIES - Taba, Navid Hashemi; Ow, Siew Hock (Malaysian Journal of Computer Science, 2019)
This research is aimed at introducing an enhanced inspection model known as Improved Software Inspection Model (ISIM) by making some enhancements to overcome or reduce the weaknesses identified in Formal model. ISIM includes a method of selecting suitable inspectors based on their expertise and work experience; provide a database that stores information on potentials; has a database that stores the possible causes of each of the defects stored in the defect database; and incorporates a few enhancements in the inspection process. To facilitate the selection of suitable inspectors and the inspection process, an inspection tool was developed using PHP with MySQL as database management system. To determine whether the use of ISIM can improve the inspection process, the quality of the process was evaluated using paired T-test which compares the differences between Formal and ISIM models, in terms of the number of defects detected, inspection time, and the productivity of the inspectors. Two case studies were conducted in two companies and inspections were carried out on two software development projects to collect the data needed for the statistical test. The statistical test results show that at ï¡ = 0.05, the mean values of the number of defects are detected; the inspection time; and the productivity of the inspectors when using Formal and ISIM are 19.78 and 28.13; 220.97 minutes and 213.69 minutes; and 0.0891 and 0.1328, respectively. This shows that there are significant improvements in the number of defects detected (i.e. difference = 8.35; 42.21%), and productivity of the inspectors (i.e. difference = 0.0437; 49.05%). However, there is only a slight improvement in the inspection time. It can be concluded that ISIM together with its tool improve the quality of inspection process in the two case studies.